Development of Vision-Based Autonomous UAV for Railway Tracking - Guclu, Emre; Aydin, Ilhan; Akin, Erhan (Institute of Electrical and Electronics Engineers Inc., 2021)
Railway transportation is commonly used today. The reason for this common use is that it is a cheap and safe mode of transportation. Defects in railways have a significant impact on safety. In recent years, automatic inspection systems are recommended for fast and reliable inspection of defects in railways. Automatic inspection systems are based on the process of collecting images from the railway and examining these images with various techniques. Image collection can be done in various ways. UAVs can be used for defect detection in terms of speed and cost. This study presents an autonomous cruise control mechanism for tracking the railway and collecting images using UAV. It is important to develop a suitable controller as it directly affects the overall response time, accuracy and rail tracking performance of the UAV. In this study, the rail lines were determined by using Gabor filter from the images taken from the UAV. Right and left rails were determined by forming two different Gabor kernels. Then, the vanishing point was found from the intersections of the obtained rail lines on the horizon. The obtained vanishing point was followed by the UAV at a constant speed using a PID controller. Experimental results have shown that the UAV successfully follows the railway by centering. © 2021 IEEE.
2021 International Conference on Innovation and Intelligence for Informatics, Computing, and Technologies, 3ICT 2021 -- 29 September 2021 through 30 September 2021 -- Virtual, Online -- 173514
Keywords: autonomous systems; PID controller; railway safety; unmanned aerial vehicles; vanishing point